2005
DOI: 10.14219/jada.archive.2005.0288
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three face masks in preventing inhalation of airborne contaminants in dental practice

Abstract: Dentists should be aware that a certified particulate respirator can provide them with superior filtering protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 13 publications
0
32
1
9
Order By: Relevance
“…Potentially hazardous bioaerosols can also be reduced by using an air cleaning system [ 5 , 19 ]. Some research shows that personal particulate respirators (certified in accordance with European Committee on Standardization standard EN 149:2001) are much more effective than high-quality surgical masks commonly used in dental practice [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially hazardous bioaerosols can also be reduced by using an air cleaning system [ 5 , 19 ]. Some research shows that personal particulate respirators (certified in accordance with European Committee on Standardization standard EN 149:2001) are much more effective than high-quality surgical masks commonly used in dental practice [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Checci et al . [ 20 ] concluded that there should be improved knowledge of immunity status of dental staff and a better vaccination programme. Additionally, past history of infection and immunization history should be known for each individual dental care professional [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to data published previously for dentists in the United States of America (USA) 29) . Certified particulate respirators have been shown to have superior filtering protection compared to high quality surgical masks in the dental setting 36) . If masks are used, face seal masks have been shown to protect against and reduce the exposure to aerosolised microorganisms 37) .…”
Section: Personal Protective Measuresmentioning
confidence: 99%
“…The report of a cluster of dentists with IPF, as well earlier reports of other respiratory hazards, emphasizes the need for proactive measures to prevent occupational respiratory complications in dental healthcare workers. Use of high‐speed evacuation and new improved masks are important considerations for all dental personnel who are exposed to aerosols in clinical or laboratory settings. The need for continuous preventive measures is illustrated by the occurrence of IPF in dentists who were older, and had potential exposure over a number of decades.…”
mentioning
confidence: 99%